Design of the Refrigeration System for the Liquid Smoke Distillation Machine at BUMDES Nusa Serasan, Sungai Lilin District, Musi Banyuasin Regency - Pangestu, Wahyu Adjie; Firdaus, Firdaus; Sundari, Ella (Yayasan Insan Mulia Bima, 2025)
The liquid smoke making flute is useful for helping entrepreneurs distill the processed coconut shells that are burned, namely Liquid smoke is a versatile substance, One of its applications is in the freezing process of rubber latex. It helps in preserving the latex by preventing oxidation and degradation, ensuring better quality and longevity during storage. The lower the water temperature in the liquid smoke condensing media, the higher the liquid smoke yield, Therefore, to enhance the yield of liquid smoke, a refrigeration system is implemented to optimize both the manufacturing and marketing processes of the product. This system helps maintain consistent quality, improve efficiency, and support larger-scale production and distribution., which initially uses water with a temperature of ± 30° C so as to increase economic income in the BUMDes and the planning stage of the tool using CAD assistance as the software medium for designing a refrigeration system on a liquid smoke distiller machine at BUMDes Nusa Serasan with an evaporation temperature of 6 °C and a condensation temperature of 49 °C and a targeted Actual COP of 2.76 and Carnot COP of 5.46 using refrigerant R22 to cool water with a capacity of 180 L where the refrigeration unit will operate for 2 hours for the cooling process.